Pompeii [videorecording (DVD)] - Batchler, Janet Scott; Batchler, Lee; Johnson, Michael Robert (Screenwriter); Harington, Kit, 1986-; Browning, Emily, 1988-; Sutherland, Kiefer, 1966-; Harris, Jared, 1961-; Graham, Currie, 1967-; Akinnuoye-Agbaje, Adewale, 1967-; Roiz, Sasha, 1973-; Moss, Carrie-Anne, 1970-; Lucas, Jessica, 1985-
Set in 79 A.D., Pompeii tells the epic story of Milo, a slave turned invincible gladiator who finds himself in a race against time to save his true love Cassia, the beautiful daughter of a wealthy merchant who has been unwillingly betrothed to a corrupt Roman Senator. As Mount Vesuvius erupts in a torrent of blazing lava, Milo must fight his way out of the arena in order to save his beloved as the once magnificent Pompeii crumbles around him.